2003
DOI: 10.1161/01.cir.0000080322.67408.b4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Phase Singularities in Ventricular Fibrillation

Abstract: Background-Multiple excitation wavelets are present during ventricular fibrillation (VF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 36 publications
8
76
1
Order By: Relevance
“…Optically recorded voltage signals were spatiotemporally filtered to reduce noise. 4,5 Phase mapping 7 was performed to evaluate the location and evolution of phase singularities (PSs) in VF. For cumulative PS display (ie, a PS map) over long acquisition intervals (typically 600 frames), PSs were identified by an automated PS tracking algorithm.…”
Section: Protocol I (N‫:)52؍‬ With a Single Cameramentioning
confidence: 99%
See 1 more Smart Citation
“…Optically recorded voltage signals were spatiotemporally filtered to reduce noise. 4,5 Phase mapping 7 was performed to evaluate the location and evolution of phase singularities (PSs) in VF. For cumulative PS display (ie, a PS map) over long acquisition intervals (typically 600 frames), PSs were identified by an automated PS tracking algorithm.…”
Section: Protocol I (N‫:)52؍‬ With a Single Cameramentioning
confidence: 99%
“…2 However, the nature of this focal source during type 2 VF remains unclear. We [3][4][5] previously demonstrated that the papillary muscle (PM) can serve as a site for anchoring reentry. An anchored stationary scroll wave can have a longer life span and can function as a mother rotor.…”
mentioning
confidence: 99%
“…The anatomic heterogeneities, which are naturally present, also facilitate conduction blocks and wavebreaks through the source-sink mismatches. 13 For example, epicardial coronary arteries, 14 papillary muscles, 15 transmural sites with abrupt fiber orientation changes, 16 and increased fibrosis resulting from cardiomyopathy 17 can all serve as sites of wavebreaks. With the more recent appreciation that dynamic factors related to electrical restitution also play a key role in facilitating wavebreak, an updated version of the Multiple Wavelet Hypothesis emphasizes that the synergy between dynamic factors and preexisting tissue heterogeneities are the fundamental cause of wavebreaks perpetuating VF.…”
Section: Multiple Wavelet Hypothesismentioning
confidence: 99%
“…It was reported that such anatomical obstacles included epicardial vessels, ridges of endocardial trabeculae and papillary muscle insertions 12 . This patient had at least three monomorphic VTs (Figs.…”
Section: Discussionmentioning
confidence: 99%